Education after Dewey - Fairfield, Paul, 1966- (Continuum International Pub. Group, 2009)
This study re-examines John Dewey's philosophy of education, and asks how well it stands up today in view of developments in Continental European philosophy. Do Martin Heidegger's statements on the nature of thinking compel a re-examination of Dewey's view? Does Hans-Georg Gadamer's philosophy of experience advance beyond Dewey's experimental model? How does a Deweyan view of moral or political education look in light of Hannah Arendt's theory of judgment, or Paulo Freires's theory of dialogical education? Part One of this study looks at Dewey's conceptions of experience and thinking in connec.